Religion, humility, and democracy in a divided America - Braunstein, Ruth, 1981- (Political power and social theory., 2019)
Strong religious convictions motivate citizens to engage in American public life, and are viewed as a source of closed-mindedness and a driver of political polarization. This book combines theoretical reflections on this tension, empirical studies examine how a range of religious actors balance conviction with humility in their political work.